1997
DOI: 10.1073/pnas.94.13.7103
|View full text |Cite
|
Sign up to set email alerts
|

Purified vesicles of tobacco cell vacuolar and plasma membranes exhibit dramatically different water permeability and water channel activity

Abstract: The vacuolar membrane or tonoplast (TP) and the plasma membrane (PM) of tobacco suspension cells were purified by free-f low electrophoresis (FFE) and aqueous two-phase partitioning, with enrichment factors from a crude microsomal fraction of >4-to 5-fold and reduced contamination by other cellular membranes. For each purified fraction, the mean apparent diameter of membrane vesicles was determined by freeze-fracture electron microscopy, and the osmotic shrinking kinetics of the vesicles were characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
137
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 32 publications
7
137
1
1
Order By: Relevance
“…Although water channels have been less studied in plants, a similar P f /P d ratio has been found for the root tonoplast and a lower one (about 3) for the root plasma membrane [40]. The high P f /P d ratio was attributed to a much higher P f determined for the tonoplast than for the plasma membrane [41]. However, later studies indicated similar P f values for the two types of membranes [42,43], emphasizing the importance of the isolation procedure for plasma membrane vesicles.…”
Section: Analysis Of Water Permeability Of the Thylakoid Membranementioning
confidence: 68%
See 2 more Smart Citations
“…Although water channels have been less studied in plants, a similar P f /P d ratio has been found for the root tonoplast and a lower one (about 3) for the root plasma membrane [40]. The high P f /P d ratio was attributed to a much higher P f determined for the tonoplast than for the plasma membrane [41]. However, later studies indicated similar P f values for the two types of membranes [42,43], emphasizing the importance of the isolation procedure for plasma membrane vesicles.…”
Section: Analysis Of Water Permeability Of the Thylakoid Membranementioning
confidence: 68%
“…[40][41][42][43]), to our knowledge, there is no measure of these two water permeability parameters for thylakoids. Nevertheless, the s a parameter for mean lifetime of water inside the thylakoid lumen has been measured using NMR by two independent laboratories [45,46] Table 2, volumes and areas from the literature [47,48], the apparent P 0 d for the chloroplast envelope and the erythrocyte plasma membrane were also calculated, and found to be only slightly lower than the experimentally determined P d values for the same type of membranes (Table 2).…”
Section: The Diffusional Water Permeability Of the Thylakoid Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Mercury reversibly inhibits the bulk water transport across membranes in animal cells (Pratz et al, 1986;Meyer and Verkman, 1987) and plant cells (Maggio and Joly, 1995;Carvajal et al, 1996;Maurel et al, 1997;Niemietz and Tyerman, 1997). This reversible inhibition is used to demonstrate the existence of proteinaceous water channels (Chrispeels and Maurel, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…sensitive aquaporin activity have also been carried out with stop-flow spectrometry using membrane vesicles (Maurel et al, 1997 ;Niemietz & Tyerman, 1997). Those results suggest a higher participation of Hg-sensitive water channels in tonoplast than in plasma-membrane water transport.…”
mentioning
confidence: 89%